Effect of saliva exposure time on the abrasion resistance of enamel eroded by acidic chlorinated water - Witchutanonth, Apinya; Prapansilp, Woranun; Rirattanapong, Praphasri (Mahidol Dental Journal, 2024)
Objectives: To evaluate saliva exposure time on the abrasion resistance of enamel eroded by acidic chlorinated water Materials and Methods: This experimental study used forty human premolars. The specimens were exposed to acidic chlorinated water and randomly assigned into 4 groups (n=10): Group-1; 0-minute saliva immersion and brushed (0MinImmBr); Group-2; 15-minutes saliva immersion and brushed (15MinImmBr); Group-3; 30-minutes saliva immersion and brushed (30MinImmBr); and Group-4; 60-minutes saliva immersion and brushed (60MinImmBr). Each group was evaluated using a Knoop hardness tester at baseline, post-erosion, post-saliva immersion, and post-toothbrushing. The length of each indentation obtained from the Knoop hardness testing was used to calculate the depth of the indentation and to determine surface enamel loss. One-way repeated ANOVA, One-way ANOVA, and LSD multiple comparison tests were used and the significance level was set at 0.05. Results: The 60MinImmBr group demonstrated the significantly highest Knoop microhardness values among the post-saliva immersion and post-tooth brushing procedures. Statistical analysis revealed no significant difference in surface microhardness after these two procedures (p<0.05) in the 60MinImmBr group. In contrast, in the other 3 groups, the surface microhardness before and after toothbrushing was significantly different. The mean surface enamel loss was significantly lowest in the 60MinImmBr group compared with the other groups. The mean surface enamel loss between the 0MinImmBr and 15MinImmBr groups was not significantly different (p<0.05), however, it was significantly higher compared with the 30MinImmBr and 60MinImmBr groups. Conclusions: The abrasion resistance of eroded enamel caused by acidic chlorinated water increased over time and at least 60 min should elapse before tooth brushing.